PKM BADAN PELESTARIAN PUSAKA INDONESIA (BPPI) DALAM PEMETAAN KAWASAN SUBAK SELAT - Cok Agung Yujana; Agus Kurniawan; Putu Gede Suranata (Universitas Warmadewa, 2022)
One of the interesting natural attractions to visit in Bali is Balinese terraced rice fields and an agricultural irrigation system known as subak. Subak as an irrigation system, the subak system is continuously undergoing a transformation process because its environment influences it. UNESCO recognition is Cultural Landscape of Bali Province: Subak as Manifestation of Tri Hita Karana Philosophy. The meaning of UNESCO's recognition is that the philosophy of Tri Hita Karana (THK) is developing in Bali. At present, the rice field area managed by subak has decreased due to land conversion. Several rice fields have now changed their function to become residential, industrial, tourist facilities, and other uses. As an effort to prevent the degradation of subak conditions, the government has made various efforts but has not been able to overcome land conversion. This effort must be assisted by all elements of society so that subak consistency is maintained in Bali. One agency that focuses on subak conservation efforts is the Indonesian Heritage Preservation Agency (BPPI). BBPI routinely conducts subak schools through the Bali International Field School for Subak (BIFSS) activities. BBPI as a partner in this PKM publishes various books related to subak conservation. Education about subak is one of the efforts to preserve subak. The implementation of this collaboration involves FTP's involvement in the BIFSS 2021 activities, which will take place in December 2021 in Subak Selat, Karangasem Regency. From the discussions carried out, in an effort to preserve subak, a Map of the Subak Strait Area is needed, including mapping of paddy fields and irrigation infrastructure. This map forms the basis for the strategy for preserving and developing the Subak Strait as a tourist attraction as well as efforts to increase the value of Subak.